A Pulse Generation Framework with Augmented Program-aware Basis Gates and Criticality Analysis - Chen, Yanhao; Jin, Yuwei; Hua, Fei; Hayes, Ari; Li, Ang; Shi, Yunong; Zhang, Eddy Z. (Proceedings - International Symposium on High-Performance Computer Architecture, 2023)
Near-term intermediate-scale quantum (NISQ) devices are subject to considerable noise and short coherence time. Consequently, it is critical to minimize circuit execution latency and improve fidelity. Traditionally, each basis gate of a transpiled circuit is decoded into a fixed episode of the device control pulses. Recent studies investigate the merged pulse generation method for customized gates through quantum optimal control (QOC). In this work, we propose PAQOC, a novel QOC framework that can (i) exploit an augmented program-aware (APA) basis gate set for the tradeoff between compilation time and circuit performance, (ii) prune the search space based on a criticality-centric analytical model and experiment observations we learned from 150 benchmarks. Evaluations using seventeen applications show that PAQOC can achieve an average 54% reduction of the circuit latency, on average 43% reduction in compilation overhead, and a 1.27× improvement in fidelity. PAQOC is available on GitHub 1 .